The impact of highly pathogenic avian influenza H5N1 virus infection on dairy cows - Felipe Peña-Mosca; Elisha A. Frye; Matthew J. MacLachlan; Ana Rita Rebelo; Pablo S. B. de Oliveira; Mohammed Nooruzzaman; Melanie Prarat Koscielny; Michael Zurakowski; Zoe R. Lieberman; William M. Leone; François Elvinger; Daryl V. Nydam; et al. (Nature Communications)
Abstract Highly pathogenic avian influenza (HPAI) H5N1 virus has been associated with severe mastitis in dairy cows, leading to decreased milk production. Here we investigated the impact of H5N1 virus infection in health and production parameters in an affected dairy herd in Ohio. Clinical disease, which lasted for about three weeks, was recorded in 20.0% (777/3876) of the adult cows. Milk losses of ~900 kg per cow were recorded in affected cows during a 60 day-post-outbreak period. Seroprevalence was 89.4% (570/637) in the herd, with 76.1% (485/637) of seropositive animals being subclinically infected. Clinically affected cows presented an increased risk of death (6 times) and of premature herd removal (3.6 times) when compared to non-clinical cows. Economic losses due to decreased milk production, mortality, and early herd removal were estimated at $950 per clinically affected cow for a total cost of ~$737,500 for the herd during the observation period. Our results demonstrate a production impact lasting at least 60 days post-clinical diagnosis and major financial consequences of HPAI H5N1 virus infection to dairy farms.